Effect of Movement Games on Physical Fitness of Children with Intellectual Disabilities - Larysa Kuznetsova; Sergii Trachuk; Viacheslav Semenenko; Olha Kholodova; Liudmyla Podosinova; Mariia Brychuk; Oleg Varenyk; Halyna Kedrych (OVS LLC, 2022)
Research purpose. The study was aimed at investigating the effect of the proposed technology using movement games on the physical and psychomotor fitness of young schoolchildren with intellectual disabilities.  Materials and Methods. Fourty children from an orphan asylum in Smila, Cherkasy region (Ukraine) participated in the study. All children were divided into two groups: control and experimental; all of them had been diagnosed with moderate-grade oligophrenia and were 2nd and 3rd graders (age 9-12 years). The control group consisted of 22 pupils, including 11 boys and 11 girls. The experimental group consisted of 18 pupils, including 9 boys and 9 girls. The following research methods were used to solve the problems set in the paper: analysis and generalization of information from special scientific literature, pedagogical research methods, method of comparison and similitude, psychoemotional state and psychomotor development research methods, methods of mathematical statistics.  Results. The study results set forth in the paper will allow stating the fact that lessons with the use of movement games have a positive effect on the physical and psychomotor fitness of young schoolchildren with intellectual disabilities, which ensures their social adaptation in the context of growth.  Conclusions. Increasing the time spent on playing games not only in classes but also in extracurricular activities had a positive effect that found expression in the improvement of the children's health and psychoemotional condition, which is the main component of the behavior of a child with mental disabilities. It can be stated that, after using the proposed movement games, the indicators of the pupils' psychomotor and mental condition, memory, perception of reality and attention improved in the positive dynamics of their physical fitness. It was found that the number of nervous breakdowns, depressive states and symptoms of stress decreased during the selected movement games.